Early Triassic (Induan–Olenekian) conodont biostratigraphy, global anoxia, carbon isotope excursions and environmental perturbations: New data from Western Australian Gondwana - Metcalfe, I.; Nicoll, R.; Willink, R.; Ladjavadi, M.; Grice, Kliti (Elsevier Science BV, 2013)
The Early Triassic Induan–Olenekian Stage boundary (Dienerian–Smithian sub-stage boundary) has been identified at a depth of 2719.25 m in the petroleum exploration well Senecio-1 located in the northern Perth Basin, Western Australia. Conodont faunas represent three conodont zones in ascending order, the Neospathodus dieneri Zone, the Neospathodus waageni eowaageni Zone and the Neospathodus waageni waageni Zone. The Induan–Olenekian (Dienerian–Smithian) boundary is placed at the base of the Neospathodus waageni eowaageni Zone equivalent to the first appearance of Neospathodus ex. gr. waageni utilised elsewhere and adopted by the IUGS ICS Triassic Subcommission to define the base of the Olenekian. Bulk kerogen δ13C carbon isotopes define a positive peak of c. 4 per mille that essentially coincides with the Induan–Olenekian boundary as seen in proposed Global Stratotype Sections and Points (GSSPs) in South China and Spiti, India demonstrating the global utility of this level for correlation. An anoxic zone is recognised in the lower part of the Senecio-1 core and the upper limit of this zone is dated as late Induan (late Dienerian). Temporal and spatial mapping of marine anoxia and dysoxia globally demonstrates that pulses of dysoxia/anoxia affected shallow-marine zones at different times in different locations. Dysoxia/anoxia in the shallow-marine environment appeared in the latest Permian at the extinction level, later than in the deep-marine environment, and appears to be largely restricted to the Induan (Griesbachian and Dienerian) and early Olenekian (Smithian).Temporally and geographically restricted upwelling of an oxygen minimum zone into the ocean surface layer due to environmental perturbations including extreme global warming, increased terrestrial chemical weathering intensity and continental erosion, sea level rise, and changes in marine nutrient inventories and productivity rates, is interpreted as a likely cause of observed variation in shallow-marine dysoxia/anoxia in the Early Triassic.